The European Transparency Requirement and the Inner Contradiction of General Terms and Conditions: Demonstration and Dissolution of a Conflict - Sharei, Mika (Teisė, 2025)
Requirements of transparency lie at the core of the European General Terms and Conditions regulation. This it not only a legal policy decision. Rather, transparency is a necessary flipside to the instrument’s (sociologically speaking) unilateral mode of creation. At the same time, General Terms and Conditions are made for an unspecified number of addressees and cases. This nature collides with the need for transparency, as it for its part calls for more complex and thus less transparent formulations. The main question arising from this contradiction is as follows: What should be the appropriate standard of transparency in the General Terms and Conditions? This is directly linked to the solution of the conflict. For this, the approach of the jurisprudence is analysed and assessed. Ultimately, its restriction of transparency requirements by what is possible under the individual circumstances, will be affirmed, as it strikes an optimal balance between protecting the counterparty of the user of the General Terms and Conditions and allowing for effective and efficient transactions.